2020
DOI: 10.1002/nau.24558
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and noninvasive test parameters that clinically differentiate detrusor underactivity from bladder outlet obstruction without a pressure‐flow‐based diagnosis in men with lower urinary tract symptoms

Abstract: Aim: To examine the symptoms and noninvasive test parameters that clinically differentiate detrusor underactivity (DU) from bladder outlet obstruction (BOO) without using a pressure-flow study (PFS) in male patients with lower urinary tract symptoms. Methods: We examined 909 men who underwent PFS and also had the following data: International Prostate Symptom Score (IPSS), free uroflowmetry, postvoid residual (PVR), and prostate volume (PV). Using these data, significant symptoms and noninvasive test parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
(45 reference statements)
0
15
4
Order By: Relevance
“…The differences in age and PV between DU and BOO were consistent with previous studies. 5,6 A lot of clinical and experimental data have shown that detrusor muscle contractile force declines with aging 7 and also that PV correlated significantly, yet slightly, with the obstruction grade. 8,9 Many previous studies have attempted to diagnose BOO due to prostatic enlargement using noninvasive parameters without PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in age and PV between DU and BOO were consistent with previous studies. 5,6 A lot of clinical and experimental data have shown that detrusor muscle contractile force declines with aging 7 and also that PV correlated significantly, yet slightly, with the obstruction grade. 8,9 Many previous studies have attempted to diagnose BOO due to prostatic enlargement using noninvasive parameters without PFS.…”
Section: Discussionmentioning
confidence: 99%
“…C Interrupted alone pattern Namitome showed the predicted probability of DU using five factors including age, PV, the symptoms of urgency and weak stream, and Qmax. 5,6 In their studies, the age of 74 years and 30 to 35 mL of PV were determined as the cutoff values. Because both DU and BOO could lower the flow rate and prolong the flow time, the question arose whether the conventional parameters on UFM such as Qmax, Qave, or VT might have limitations to differentiate DU from BOO.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DU does not always reflect a subjective complaint as Takahashi et al reported that the urgency score was lower in DU than in non-DU patients. 29 In fact, IPSS was not statistically associated with poor voiding patterns in LCS (Table 3). Confounding factors other than excluded comorbidities must also affect IPSS (eg, age, metabolic syndrome, and cardiovascular disease).…”
Section: Discussionmentioning
confidence: 91%
“…Attention needs to be paid to the limitation of lacking specific orthopedic symptoms or neurological findings other than JOA scores. Additionally, DU does not always reflect a subjective complaint as Takahashi et al reported that the urgency score was lower in DU than in non‐DU patients 29 . In fact, IPSS was not statistically associated with poor voiding patterns in LCS (Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…Recently, some studies have aimed to identify the characteristic symptoms that can predict the presence of urodynamic DU. [3][4][5][6] A study based on a large European database of urodynamic studies (UDS) identified decreased sensation, in addition to strain-to-void and incomplete bladder emptying, as the characteristic symptoms of men with DU. 4 Takahashi et al 5 reported that older age, smaller prostate volume, and fewer urgency symptoms were significant predictive factors for differentiating DU in men with LUTS.…”
mentioning
confidence: 99%